Resources Optimization in a Facility Management: A case company in the Service Industry - Ndulango, Josephat (My University, 2025)
Resource optimization in the service industry involves effectively utilizing resources to enhance productivity and meet customer satisfaction by providing high-quality ser-vices. Maximizing resource utilization benefits both the company and its customers by offering high-quality services at reasonable prices. The current thesis focuses on re-source optimization in the service industry. Case Company X, a Finnish company, has operated for approximately 40 years and primarily operates in different Finnish cities, Helsinki, Turku, Tampere, Vaasa, and Lahti. The company specializes in facility manage-ment, specifically cleaning services for hotels, restaurants, nightclubs, pubs, offices, healthcare facilities, and construction sites. Thus, the thesis addresses the research question: How can resources be optimized to enhance productivity and reduce opera-tional costs in a company? To answer the research question, semi-structured interviews were conducted with an operational manager and observations and opinions from workers at work sites in the Pirkanmaa region. The data were analyzed based on their content, which enabled the researcher to draw conclusions that reflected the inter-views. This study examines the company's operational challenges and issues and explores how it can optimize resource utilization to minimize operational costs. It provides prac-tical guidelines for the company to mitigate its operational cost challenges. Further-more, the results revealed that the services sector's contribution to the economy needs synchronization of technology use. This dramatically impacts service production and cost reduction in different areas to harmonize the services business’s operation. In the final analysis, cost reduction in the operation department, logistics, recruitment, and employee retention is essential for successful business strategies and financial health. The studies suggested that future research is needed to identify types of clean-ing, maintenance costs, and the necessary skills required in modern buildings.
Keywords: services; resources; customer satisfaction; costs; facilities management; evaluation; business operations; recruitment of employees; staff; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management